Online Antagonism of the Alt-Right in the 2016 Election - Niko Heikkilä (European Journal of American Studies)
Buoyed by the populist campaign of Donald Trump, the “alt-right,” a loose political movement based around right-wing ideologies, emerged as an unexpected and highly contentious actor during the election cycle. The alt-right promoted controversy through provocative online actions that drew a considerable amount of media attention. This article focuses on the role of the “alt-right” in the 2016 election by examining its visual and rhetorical efforts to engage the political mainstream in relation to the campaigns of Donald Trump and Hillary Clinton. In particular, the alt-right’s unique style and internal jargon created notable confusion and also attracted interest by the media, while its promotional tactics included the use of social media and Internet memes, through which the movement came to epitomize online antagonism in the 2016 election.